2014
DOI: 10.1101/gad.233791.113
|View full text |Cite
|
Sign up to set email alerts
|

miR-99a/100∼125b tricistrons regulate hematopoietic stem and progenitor cell homeostasis by shifting the balance between TGFβ and Wnt signaling

Abstract: Although regulation of stem cell homeostasis by microRNAs (miRNAs) is well studied, it is unclear how individual miRNAs genomically encoded within an organized polycistron can interact to induce an integrated phenotype. miR-99a/100, let-7, and miR-125b paralogs are encoded in two tricistrons on human chromosomes 11 and 21. They are highly expressed in hematopoietic stem cells (HSCs) and acute megakaryoblastic leukemia (AMKL), an aggressive form of leukemia with poor prognosis. Here, we show that miR-99a/100~12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
164
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(170 citation statements)
references
References 71 publications
(69 reference statements)
2
164
0
Order By: Relevance
“…Hence, it is likely that other miR-125b targets beyond Vps4b and Mapks will contribute to the oncogenic effects that we described here. In this regard, it is interesting that in hematopoietic stem cells (HSCs), miR-125b was recently found to regulate multiple target genes involved in TGF-b signaling (Emmrich et al 2014).TGF-b signaling also functions in skin tumorigenesis, and Smad4, one of the miR-125b targets in HSCs, was also among our miR-125b targets (Supplemental Table S1, sheet 1). Another previously reported miR-125b target is TACSTD2, which functions in MAPK signaling (Nakanishi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it is likely that other miR-125b targets beyond Vps4b and Mapks will contribute to the oncogenic effects that we described here. In this regard, it is interesting that in hematopoietic stem cells (HSCs), miR-125b was recently found to regulate multiple target genes involved in TGF-b signaling (Emmrich et al 2014).TGF-b signaling also functions in skin tumorigenesis, and Smad4, one of the miR-125b targets in HSCs, was also among our miR-125b targets (Supplemental Table S1, sheet 1). Another previously reported miR-125b target is TACSTD2, which functions in MAPK signaling (Nakanishi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the mammalian genome, three distinct miRNAsmiR-99a/100, let-7a/c, and miR-125b-form an adjacently positioned and cotranscribed polycistronic miRNA cluster (Emmrich et al 2014) whose alterations are frequently found in cancers (Calin et al 2004). While let-7 family miRs are well-established suppressors (Johnson et al 2005;Mayr et al 2007), the roles of other individual members of this miR cluster in cancer are less clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By regulating the balance of these two signaling pathways, the miR-99a/100∼125b tricistronic miRNAs are reported to promote human HSCs expansion and to favor megakaryocytic diferentiation [143]. Additionally, miR-126 regulates HSC proliferation and diferentiation by targeting PI3K/AKT/mTOR signaling [131].…”
Section: Further Cytokine and Small Molecule Addition To Expand Umentioning
confidence: 99%
“…Wnt and TGF pathways also have opposing roles in regulating the balance between HSC selfrenewal, quiescence, and diferentiation [143], and these are controlled by miRNAs. By regulating the balance of these two signaling pathways, the miR-99a/100∼125b tricistronic miRNAs are reported to promote human HSCs expansion and to favor megakaryocytic diferentiation [143].…”
Section: Further Cytokine and Small Molecule Addition To Expand Umentioning
confidence: 99%